Computational mathematics in engineering careers: study of electrical circuits from the perspective of interdisciplinary teaching. - Gago, Eduardo Alberto; D’Alessandro, Lucas Iván; Szekieta, Paola Andrea (WSEAS, 2023)
The new challenges of the educational engineering framework pretend to encourage the interdepartmental integration and interaction between basic sciences and the module of applied technology subjects. This paper presents a learning approach of interdisciplinary learning in the teaching of trigonometric functions, with special emphasis on the sinusoidal function, showing how the transformation of this function is related to fundamental concepts in the training of electrical energy engineers. The product of trigonometric functions makes it possible to analyze the instantaneous power of passive linear electric circuits and highlight the importance of studying the phase angle between voltage and current associated with the inductive or capacitive nature of the circuit. The development of the contents in the class contemplates the interdisciplinary and integrative aspect that must be implemented from the basic cycle as a bridge towards the applications of mathematics, articulating the problems of Engineering and the use of technologies in teaching.
Keywords: Ingeniería eléctrica; Enseñanza de la matemática; Interdisciplinaridad; Trigonometría; Circuitos eléctricos; Simulación